“Push and Pull”: Biomechanics of the Pollination Apparatus of Oncidium spp. - Thielen, Marc; Voigt, Dagmar; Gallenmüller, Friederike; Speck, Thomas; Gorb, Stanislav (Frontiers in Mechanical Engineering, 2021)
Comprising ca. 28,000 species the Orchidaceae constitute one of the most species-rich plant families. Orchids differ from other monocotyledons i.a. in the formation of so-called pollinaria, which are entities consisting of pollen grains aggregated into compact pollinia and accessory structures, a viscidium and mostly also a pollinium stalk. The viscidium releases an adhesive material that attaches the pollinarium to a pollinator. Pollinaria are part of a complex pollination apparatus that enables the orchids to colonize niches in which only a few individuals of the respective pollinator occur infrequently. Because the aggregated pollen grains are removed from the flower at once, the development of a mechanical barrier ensuring that only suitable pollinators are able to access the flowers - and more importantly - to remove the pollen are important selective traits. In this paper we describe the functional morphology of the pollination apparatus in two orchid species, Oncidium wentworthianum and O. otogaya, by experimentally mimicking the pollination process. Furthermore, we analyzed the mechanical resistance of this apparatus by means of force measurements and showed that it most probably constitutes a hierarchical two-stage barrier. The first stage consists of the presence of the anther cap that not only protects the pollinia, but also serves to prevent premature removal of young and unripe pollinaria from the flower. As soon as the pollinaria are ripe, the anther cap sheds and the second stage of the mechanical barrier takes effect, a severable bond between pollinarium and rostellum. This bond can be overcome by a potential pollinator, applying a load of at least 10.8 mN (O. otogaya) or 12.6 mN (O. wentworthianum), respectively, on the viscidium which at the same time disengages the pollinarium from its anchorage. The adhesive material produced by the viscidium creates sufficient adhesive contact between pollinarium and pollinator. Potential pollinators, such as Centris spp. or Trigona spp. bees, should be well able to exert such forces by pushing their head/forebody into the orchid flowers. Thus, whether a pollinator is able to detach the pollinarium depends on both how forcefully it can push and how strongly it can pull the orchid pollination apparatus.